STRATEGI KAMPANYE “TILIK JIWA” DALAM MENINGKATKAN AWARENESS DAN PARTISIPASI LAYANAN SKRINING KESEHATAN MENTAL OLEH DINAS KESEHATAN KOTA SEMARANG - Sonia Nazwa Auranti; Nurul Hasfi (Interaksi Online, 2026)
Mental health remains a taboo topic, especially among young people aged 18–25 in theBanyumanik and Tembalang districts of Semarang City. This is due to low awareness,knowledge, and increased negative stigma towards mental health screening services. The lowlevels of these three indicators have resulted in low community participation in mental healthscreening services. Therefore, in collaboration with the Semarang City Health Office, wedesigned the Tilik Jiwa campaign using a social marketing approach through an integratedcommunication strategy developed through a survey of 236 people. This campaign combinesonline and offline communication strategies, such as digital campaigns on Instagram and aseries of offline activities, including mental health screening events and roadshows in 15 publicspaces. The campaign involves media planners and social media specialists to determineeffective media and design content for digital campaigns. The Tilik Jiwa campaign significantlyincreased awareness, improved knowledge, and reduced negative stigma regarding mentalhealth screening services, resulting in a 36% increase in participation with 86 more peopleinvolved in mental health screening services. These successful results highlight theeffectiveness of the communication strategies used in the Tilik Jiwa campaign.